Sn‐catalyzed silicon nanowire solar cells with 4.9% efficiency grown on glass. (13th January 2012) - Cho, Jinyoun; O'Donnell, Benedict; Yu, Linwei; Kim, Ka‐Hyun; Ngo, Irène; Cabarrocas, Pere Roca i
ABSTRACT We present a single pump‐down process to texture hydrogenated amorphous silicon solar cells. Mats of p‐type crystalline silicon nanowires were grown to lengths of 1 µm on glass covered with flat ZnO using a plasma‐assisted Sn‐catalyzed vapor‐liquid‐solid process. The nanowires were covered with conformal layers of intrinsic and n‐type hydrogenated amorphous silicon and a sputtered layer of indium tin oxide. Each cell connects in excess of 107 radial junctions over areas of 0.126 cm². Devices reach open‐circuit voltages of 0.8 V and short‐circuit current densities of 12.4 mA cm−2, matching those of hydrogenated amorphous silicon cells deposited on textured substrates. Copyright © 2012 John Wiley & Sons, Ltd.